2017
DOI: 10.1111/ijfs.13467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of butter content and baking condition on characteristics of the gluten‐free dough and bread

Abstract: Summary This study aimed to investigate effect of butter content (0–30 g/100 g flour) and baking conditions hot air baking (HA), microwave baking (MW) and hot air‐microwave baking (HA‐MW) on quality of the rice flour dough and bread. The increased butter (up to 15 g butter/100 g flour) enhanced elastic modulus (G′) and viscous modulus (G″) of dough and specific volume of bread. Additionally, the increased butter improved crust colour and reduced hardness of the bread. The HA‐MW and MW conditions were useful fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The temperature of the outer surface of the food is lower than that of traditional baking, which is not conducive to the occurrence of Maillard reaction and can provide control over the formation of TPHs. At present, the research of microwave baking is mainly focused on the effect of microwave heating on dough texture and color, the loss of water during heating, and the change of functional characteristics of dough components (12)(13)(14), However, there are few studies on the influence of microwave on the formation of TPHs in biscuits. AL-Ansi et al (15) reported that fennel or nigella to biscuits under microwave baking conditions reduced AM production more than traditional baking.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of the outer surface of the food is lower than that of traditional baking, which is not conducive to the occurrence of Maillard reaction and can provide control over the formation of TPHs. At present, the research of microwave baking is mainly focused on the effect of microwave heating on dough texture and color, the loss of water during heating, and the change of functional characteristics of dough components (12)(13)(14), However, there are few studies on the influence of microwave on the formation of TPHs in biscuits. AL-Ansi et al (15) reported that fennel or nigella to biscuits under microwave baking conditions reduced AM production more than traditional baking.…”
Section: Introductionmentioning
confidence: 99%
“…The FA compositions of the shortening, sunflower oil (SFO), oleogel/shortening blends given in Table show that shortening (specific for cake production) was found to be rich in palmitic acid (PAM) (16:0) as palm and palm kernel oil fractions are commonly applied for production of shortenings. Palm‐based shortenings are known to form β´ polymorphic forms that are regarded as better in air stabilization than other crystal structures (Bazmi et al, ; Cheong et al, ; Srikanlaya et al, ). β′ crystals are relatively small and enable to trap a larger amount of liquid oil in the crystal network and hence create a glossy surface and a smooth texture.…”
Section: Resultsmentioning
confidence: 99%
“…Slowly melting crystals provide a controlled expansion of the bubbles without rupture. When the shortening was replaced with BW10, bubbles might not be protected due to the insufficient amount of crystals, resulting in aggregation and ruptured bubbles and hence the formation of a denser cake (Brooker et al, ; Mert and Demirkesen, ; Srikanlaya et al, ; Zhou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, butter insertion inside potatoes might induce two forms of interactions; first, a continuous starch-lipid complex network that could be formed by Vander Waals hydrophilic interactions and hydrogen bonding between the carboxylic group at the end of the fatty acid chains and that of starch molecules. Second, the interactions might be compromised by a tendency of self-association among fatty acids, due to the recrystallization ability of butter that enhances the solidification effect, creating a highly consistent and stable product [20,21]. Table 2.…”
Section: Yield Stressmentioning
confidence: 99%